SISTEM INFORMASI ADMINISTRASI PEMBAYARAN SEKOLAH BERBASIS WEB PADA SMA PLUS NAHDLATUL ULAMA PANGURAGAN (INTI TALAFA, 2023)
Web-Based School Payment Administration Information System at SMA Plus NU (Nahdlatul Ulama) Panguragan is a Payment data processing application that is used as Administration at SMA Plus NU Panguragan. This application was made based on research conducted at SMA Plus NU Panguragan, this is because there is no Website that is used for Administrative data processing which is still manual using excel and the data is stored in a database so that it makes it easier to store Payment data archives. The research method used is the R&D (Research & Development) research method with a descriptive analysis approach. This application is made using Hypertext Preprocessor (PHP) and CodeIgnitter framework with MySQL database. The school Payment data processing application is used to store Administrative data at school, this Payment data processing has several features such as student profile data, class data, billing data, and transaction data, which can streamline time for Administrative management at SMA Plus NU Panguragan. The Administrator page is an Admin-level page in which there are Dashboard, Class, Student, Transaction Billing, and print menus that are used for Administrative purposes at SMA Plus NU Panguragan. The WEB- Based School Payment Administration Information System at SMA Plus NU (Nahdlatul Ulama) Panguragan can solve Administrative data management problems at school and can be an alternative solution in facilitating filing and paying bills at SMA Plus NU Panguragan.